Cerebral small vessel disease as a possibly immune-related adverse event of immunotherapy in lung cancer patients: a retrospective study - Wu, Na; Zhou, Dongmei; Guo, Xiaoyu; Liu, Jia; Liu, Jiafan; Liu, Fan; Wang, Xiaonan (Frontiers in Immunology, 2025)
BackgroundThis clinical study aims to investigate the incidence of cerebral small vessel disease (CSVD) in lung cancer patients treated with ICIs and to analyze its risk factors by comparing the clinical features and laboratory tests in ICIs-treated lung cancer patients with or without CSVD.MethodsThis retrospective study included 400 hospitalized patients from January 2018 to May 2024. All patients had confirmed lung cancer, received at least one cycle of ICIs, and underwent cranial MR imaging before and after ICIs treatment. Information from the medical records, including clinical features, MR imaging findings, laboratory tests, complications, treatment, and clinical outcomes, was extracted for analysis.Results104 (26%) patients with CSVD were confirmed and 53.25% were aged≥65 years. Risk factors identified as independent predictors of CSVD included age (OR, 1.03), stage IV (OR, 2.87), and hyperlipidemia (OR, 1.02). In the CSVD group, FT4 levels decreased significantly between baseline and at the time of CSVD diagnosis, from 13.21 ± 4.56 pmol/L to 11.01 ± 2.11 pmol/L. TSH levels increased from 4.12 ± 0.46 pmol/L to 4.78 ± 1.13 pmol/L, cysteine C levels increased from 1.01 ± 0.98 mg/L to 1.29 ± 0.86 mg/L, PLR increased from 164.93 ± 27.86 to 171.27 ± 32.29 and SII rose from 774.28 ± 53.57 to 790.65 ± 68.34. All of them had no significance in the Non-CSVD group. Further Cox regression analysis showed that hypothyroidism (HR=2.38; 95% CI:1.89-5.04, P=0.005) was independent risk factors for CSVD. The incidence of hypothyroidism was 19.5% (78/400), and 43.6% (34/78) among them had CSVD. As predictors of CSVD, the cut point for FT4 was 11.84 pmol/L, and for TSH, it was 4.23 pmol/L. In Survival Analysis, CSVD did not show a significant impact on the median progression-free survival (PFS) and overall survival (OS) of lung cancer patients.ConclusionThis study found that CSVD may be a related adverse event of immunotherapy in lung cancer patients. In addition to age≥65 years, hyperlipidemia and stage IV, hypothyroidism, elevated cysteine C levels, and elevated systemic inflammatory markers such as PLR and SII were further associated with an increased risk of CSVD.